Mechanical and ballistic properties of natural fibre-aramid hybrid laminated composites - Yahaya, Ridwan (2015)
The advantages of using natural fibres in a wide range of applications, together with environmental concerns, have led researchers to explore natural/synthetic fibre hybrid composites. In this study, a natural/synthetic hybrid composite was prepared using the hand lay-up method in a laminate configuration. Natural fibres were systematically chosen for hybridisation with the high-performance synthetic fibre, Kevlar (aramid fibre). This selection was conducted using the analytical hierarchy process (AHP), in which the cost, availability and mechanical properties were considered. The result indicates that kenaf fibres are the most potential fibres for hybridisation with Kevlar. Hand lay-up method was adopted to fabricate the kenaf/Kevlar hybrid composites. It’s followed by mechanical and ballistic test which conducted with reference to international standards. Based on this study, it was found that post-curing temperature,kenaf content and resin-hardener mixing ratio gives significant effects on the mechanical properties of kenaf-Kevlar hybrid composites.Experimental works on the effects of kenaf contents and fibre orientation indicate that woven and unidirectional kenaf fibres reinforced composites display better tensile and flexural properties as compared to the non-woven mat. It is also noticed that increasing volume fraction of kenaf fibre in hybrid composites reduces tensile and flexural properties. Based on SEM micrographs the hybrid composites failed by the typical splitting process and interfacial shear fracture. Composite with kenaf mat contains the high void in laminates and poor interfacial bonding. The research revealed that hybrid composite with Kevlar as the outer layers display a better mechanical property as compared to other hybrid composites. Hybrid composites with treated kenaf fibres resulted in higher mechanical properties than the non-treated hybrid composites. However, hybrid composites with high kenaf content show low density (0.88g/m3) and contains a high content of the voids (25.67%). After the water absorption test, the impact strength was decreased about 45.38 to 78.52%. The mechanical properties of kenaf-Kevlar hybrid composites are a function of fibre content. The hybrid composites with Kevlar-kenaf (78/22) ratio exhibited better mechanical properties compared to other hybrid composites. Ballistic measurement tests of hybrid composites were carried out by using fragment simulating projectiles at different impact and residual velocities. The highest V50 was observed in sample 14B (452 m/s), with a thickness of 12.7 mm, which exceeded that of sample 14A (295 m/s), with a thickness of 10.43 mm, by 34%. Sample 8B, with a thickness of 9.7 mm, exhibited a V50 of 393 m/s, while sample 8A, with a thickness of 8.08 mm, had a V50 of 295 m/s. In terms of the specific energy absorption, sample 8A absorbed 40.09% less than 8 Kevlar, while sample 8B absorbed 37.71% less than 8 Kevlar. The results indicate a significant decrease in energy absorption due to the addition of kenaf layers in hybrid type B. It was observed that ballistic properties increase with the thickness and areal density of the composites. Interlayer delamination was observed as the modes of failure in kenaf-Kevlar hybrid composites. Overall, the experimental results demonstrate the potential of kenaf-Kevlar hybrid composites for ballistic impact applications.